Uma fábrica de mentiras: a (in)comunicação da economia da dança - Leão, Doralice Soares (2012)
There are many thinkers who state as urgent the need to deal with culture as a productive segment (THOMPSON, 1999; BRIGGS and BURKE, 2004) and there are some initiatives aimed at a very much needed data system (BNDES (National Bank for Economic and Social Development), 2006; SEBRAE (Brazilian Service for Small Business Development), 2008) capable of providing visibility to the role the culture plays in the current scenario of capitalism (BENTES, 2007; JAMESON, 1996; SENNETT, 2006). A new field has been designed, the culture economy, which still does not have great media visibility and, within it, there is another field, which has been referred to as dance economy. However, the silence of the economic journalism and of the cultural journalism has been keeping invisible the economy-culture relationship, as well as the economy and dance relationship. With the purpose of reverting the situation, the paper is based on bibliographic review to focus on political forces that influence the dance economy (MCLUHAN, 2001; OLIVEIRA & CIANCIO, 2007). The hypothesis suggested herein is opposed to the line of thinking that discloses in seminars, meetings, congresses and festivals the status of dance economy because it questions the existence of a productive sector that can actually be conceived as dance economy. For such, the research embodies the communication forms of the events promoted on that issue between 2000 and 2012, and its theoretical ground is the Corpomídia Theory (KATZ & GREINER 2001, 2003) in order to show that the exchanges between bodies and environments around this possible existence of dance economy have been increasing (DAWKINS, 1976) without any critical thinking and, thus, contributing towards the strengthening of public policies for the culture which are incapable of promoting autonomy